Stato e società civile in Gramsci (State and Civil Society in Gramsci) - Guido LIGUORI (Polis: Revista de Stiinte Politice, 2016)
Gramsci is not, as at times has been said, the “theoretician of civil society”. Central to his reflections in the Prison Notebooks is instead the concept of the “integral State” or “extended State”, the dialectical union of State and civil society which allowed him to interpret the new social and political situation typical of much of the twentieth century. This new situation is characterized, on the one hand, by a new relationship between the economy and politics and, on the other, by the growing importance of the “apparatuses of consent” flanking the State’s traditional repressive apparatuses. For Gramsci the apparatuses of consent are sometimes public and sometimes apparently private but, in any case, their function is the same, namely to reinforce the hegemony of the dominant class, and to propagate a traditional common sense, thereby making it difficult to challenge the given set-ups of power. Since there has been a change in the State – the terrain of the struggle for power – the concept of revolution must also change: this is no longer an isolated insurrectionary event, as it was in the nineteenth century, but a long struggle for the conquest of “trenches and emplacements”, in other words the conquest of the centres that produce and extend consent.